PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KEPUASAN KERJA DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING - ERVYANA FITRI (JURNAL EKOBIS DEWANTARA, 2018)
ABSTRACT The purpose of this study is to describe: (1) the influence of transformational force on job satisfaction; (2) the influence of the transformational leadership style on organizational commitment; (3) the influence of organizational commitment to job satisfaction; (4) the influence of transformational leadership style on job satisfaction with organizational commitment debagai intervening variable. This research is a quantitative research. Population in this research is employees "Balu Oto Work Yogyakarta". The data were collected by questionnaire method. Data analysis technique used is regression technique supported by t test, path analysis test and classical assumption test with SPSS 18.00 for windows application.Result of data analysis with significance 0,05 indicate that leadership style have positive and significant effect to job satisfaction; leadership style has a positive and significant impact on organizational commitment; organizational commitment has a positive and significant impact on job satisfaction; transformational leadership style positively affects job satisfaction with organizational commitment as intervening variable.